Epidemiologija, etiologija, klinična slika in diagnostika depresije - Kores-Plesničar, Blanka (Farmacevtski vestnik, 2006)
Depressive disorder is the most common psychiatric disorder all over the world. It is frequnetly a chronic disease with high rates of recurrence and impairment of physical and social functioning. Depression also all too frequently complicates physical illness. Unfortunately, depression can often go undiagnosed and untreated. Appropriate treatment effectively promotes both an elimination of a broad spectrum of symptoms and a return to full social functioning.
Keywords: depresija (medicina); Depresivna motnja; Depressive Disorder; diagnosis; Diagnostika; Epidemiologija; epidemiology; Etiologija; etiology